1996
DOI: 10.1039/dt9960001333
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of unusual simultaneous binding of four cytosine nucleobases to copper(II) by a novel network of bifurcated hydrogen bonding

Abstract: The crystal structure of tetrakis(cytosine)copper(rI) perchlorate dihydrate has been determined. All the hydrogen atoms were obtained from Fourier-difference synthesis. The geometry around copper is a bicapped octahedron (4 + 2 + 2*). The adjacent cytosine rings are oriented head-to-tail with respect to each other and are roughly at right angles to the co-ordination plane. The exocyclic 0x0 groups form an interligand, intracomplex hydrogen-bonding network above and below the co-ordination plane with the exocyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 34 publications
(1 reference statement)
1
25
0
Order By: Relevance
“…Notwithstanding, the intramolecular 2.687(5) Å and 2.726(5) Å CuÁ Á ÁO12 distances for B and A, respectively, could be interpreted as a (4 + 1) pseudocoordination. In fact, these lengths fall inside the 2.55-2.80 Å range reported in the literature for the cytosine Cu-O bonds [21,[33][34][35][36]. This feature is also supported by the Cu-N13-C12 and Cu-N13-C14 angles: 108.1(4)/ 129.1(4)°and 106.3(4)/132.6(4)°for A and B, respectively.…”
Section: Preparation Of the [Cul(hcyt)](clo 4 )supporting
confidence: 55%
“…Notwithstanding, the intramolecular 2.687(5) Å and 2.726(5) Å CuÁ Á ÁO12 distances for B and A, respectively, could be interpreted as a (4 + 1) pseudocoordination. In fact, these lengths fall inside the 2.55-2.80 Å range reported in the literature for the cytosine Cu-O bonds [21,[33][34][35][36]. This feature is also supported by the Cu-N13-C12 and Cu-N13-C14 angles: 108.1(4)/ 129.1(4)°and 106.3(4)/132.6(4)°for A and B, respectively.…”
Section: Preparation Of the [Cul(hcyt)](clo 4 )supporting
confidence: 55%
“…It was found that the predominant metal binding site of cytosine nucleobase is the nitrogen atom N(3) (Scheme 2) [11,12,14,15,17,23,24]. In addition, the secondary interaction between copper and the O(2) exocyclic carbonyl group of cytosine also exists in a few cases [16,25,26].…”
Section: Introductionmentioning
confidence: 96%
“…These activities have guided us to prepare copper(II) complexes containing a CuN 2 Cl 2 chromophore analog to cisplatin and then to study their interactions with DNA nucleobases. Several studies have mainly focused on the direct interaction of metal salts, where M = Cu, Rh, Cd, Mn or Co, with the cytosine nucleobase and its derivative 1-methylcytosine [12][13][14][15][16][17][18][19], but not the direct nucleobase replacement of the anionic ligands on metal complexes like the cisplatin system. However, Reedijk and coworkers have studied on interactions of the octahedral ruthenium(II) complexes [cis-Ru(bpy) 2 Cl 2 ] [20] and [a-Ru(azpy) 2 -(NO 3 ) 2 ] [21] (bpy = 2,2 0 -bipyridine and azpy = 2-(phenylazo)pyridine) with 9-ethylguanine, 9-methylhypoxanthine and guanosine, which replace only one of the two anionic ligands to yield the monofunctional binding adducts.…”
Section: Introductionmentioning
confidence: 99%
“…The frozen solution EPR spectra of the complexes are axial with g i > g^> 2.0 and G = [(g i À 2)/ (g^À 2)] = 3.6 suggesting that the nearly square-based geometries observed in the solid state are retained in solution. Further, a square-based CuN 4 chromophore is expected [45,46] to show a g i value of 2.200 and an A i value of 180-200 · 10 À4 cm À1 (Table 3) and the replacement of nitrogen atom in this chromophore by an oxygen atom is expected to increase the g i value and decrease the A i value. On the other hand, incorporation of strong axial interaction as in the present complexes would increase the g i and decrease the A i values.…”
Section: Spectral Propertiesmentioning
confidence: 99%